Effect of Cleaning Process on Physical and Microbiological Air Quality in Hospital Environment: Case Study of Bhakti Dharma Husada Hospital - Febrianna, Fatima Intan; Rokhmalia, Fitri; Suryono, Hadi; Sulistio, Irwan; Sari, Ernita; Sucipto, Cecep Dani; Imami, Ahmad Daudsyah (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Surabaya, 2025)
Examination of air quality at Bhakti Dharma Husada Surabaya Hospital showed a non-conformity of standards in the LAF Room (Laminair air flow). The study aimed to analyse the physical and microbiological air quality factors in the cleaning process in the LAF (Laminair Air Flow) room. The study used an observational descriptive design with a cross-sectional approach. The study population was room air in the LAF room. The research variables included temperature, humidity, lighting, air germ count, Staphylococcus, and room cleaning process. Data collection techniques were observation, measurement, and laboratory examination. Data were analysed and presented descriptively. The study's results showed the value of the air germ number before the cleaning process was 16 CFU/m3, exceeding the required quality standard of 10 CFU/m³. Measurements after the cleaning process have met the requirements of 9 CFU/m³. Room temperature and humidity measurements before and after the cleaning process have met the quality standards of 16-25°C and 35-50%. The lighting measurement of 110.6 lux does not meet the minimum requirement of 500 lux. Environmental health officers should monitor room cleaners for compliance with the use of personal protective equipment. It is necessary to increase the intensity or modify the lighting.